ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE DU PONT SYSTEM PADA INDUSTRI FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - TONA AURORA LUBIS; . ZULKIFLI; NORIA SAPUTRI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
This study aims 1) To know the development / change of Total Debt, Total Assets, Sales, Profit After Interest and Taxes, Debt to Asset Ratio (DAR), Total Asset Turn Over (TATO), and the Net Profit Margin (NPM) of the Company at Food and Beverages industry listed in Indonesia Stock Exchange 2012-2014. 2) To determine the financial performance of companies based on analysis method of Du Pont System on Food and Beverages industry listed in Indonesia Stock Exchange 2012-2014. 3) To determine a company's financial performance ratings based method Du Pont System on Food and Beverages industry listed in Indonesia Stock Exchange 2012-2014. The object of this research are companies engaged in the Food and Beverages industry listed in Indonesia Stock Exchange 2012-2014 period totaling 15 companies. Variables used in the calculation method of Du Pont System in this study is Debt to Asset Ratio (DAR), Total Asset Turn Over (TATO), Net Profit Margin (NPM), Return On Investment (ROI) and Return on Equity (ROE) . Based on the results, it can be concluded that the financial performance of the fifteen companies in the Food and Beverages industry who possess the period 2012-2014 is the highest ranking PT. Multi Bintang Indonesia Tbk with a value of Return On Investment (ROI) in 2012 amounted to 39.36%, in 2013 amounted to 65.72%, in 2014 amounted to 35.63% and the Return on Equity (ROE) in 2012 amounted to 137, 46%, in 2013 amounted to 118.60%, in 2014 amounted to 143.53%. While the lowest-ranked in 2012 and 2013 were PT. Tri Banyan Tirta Tbk with a value of Return On Investment (ROI) in 2012 was 1.83% and in 2013 amounted to 13.05% and value of Return On Equity (ROE) in 2012 amounted to 4.82%, in 2013 by 2 , 22%. And the lowest rank in 2014 was PT. Prasidha Aneka Niaga Tbk with a value of Return On Investment (ROI) amounted to -4.54% and the Return on Equity (ROE) of -7.44%.